A new Perigrapha Lederer, 1857 from South Kazakhstan (Lepidoptera, Noctuidae) - Volynkin, Anton V.; Titov, Sergey V.; Knyazev, Svyatoslav A. (Zootaxa, 2014)
A new species of the genus Perigrapha, P. yasawii sp. n. is described from Syrdarya river valley, South Kazakhstan. The adults and male genitalia of the new and related species are illustrated.